UPAYA MENINGKATKAN KESEJAHTERAAN DI TENGAH KERAGAMAN SISWA MELALUI PENDIDIKAN MULTIKULTURAL DI SEKOLAH DASAR - Julianne Uswatun Hasanah; Sulis Nurqori’ah (Institut Agama Islam Negeri (IAIN) Bone, 2021)
In elementary school, each student certainly has different backgrounds such as different cultural backgrounds, races, socioeconomic levels, and religions so that they have different values, norms, and behaviors. The existence of diversity among high-class elementary school students makes multicultural education an effort to improve the welfare of students in the school environment with harmonious social interactions. The steps taken to find out and answer these problems, the researchers conducted a literature study related to multicultural education to the finding that diversity among students can be addressed through multicultural education which is supported by the role of teachers as educators and the integration of multicultural education in subjects and the use of learning strategies that are in accordance with the demands of multicultural education in order to achieve optimal learning outcomes by providing an understanding of attitudes in diversity for mutual respect, respect, and tolerance between friends in elementary school which is carried out both inside and outside the classroom and during learning activities and outside learning activities. Multicultural education aims so that students as the nation's next generation can have social behavior in accordance with applicable norms and valuesKeywords: diversity, student, multicultural education